PENGEMBANGAN AUGMENTED REALITY GERAKAN DASAR TARI BALI - Saka Aji; I Nengah Eka Mertayasa; Wayan Arta Suyasa (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
implement an Augmented Reality application for basic Balinese dance movements. The research method used is research and development (R&D), to develop an Augmented Reality application for basic Balinese dance movements, using the MDLC (Multimedia Development Life Cycle) method until the system testing stage. This application uses Vuforia, which is able to play sounds and display 3D objects of basic Balinese dance movements in a real-life environment using flashcards and an Android-based smartphone. The final result of this research is an application containing information and images related to basic Balinese dance movements that function as markers. An Android-based Augmented Reality application that can display dancers with basic Balinese dance positions and movements in 3D directly above the markers, complete with displays of basic Balinese dance movements and explanatory voice narration of the movements. This application can be used as a medium to introduce and preserve Indonesian culture.